Influência do tratamento com silício em sementes de sorgo granífero submetidas a estresses abióticos - Pinheiro, Paloma Rayane (2019)
In the field sorghum seeds are exposed to various environmental factors that can lead to stress, among which we have water stress and saline. Silicon (Si) due to its accumulation in the cell wall can bring several benefits to plants and serve as an attenuator to these stresses. The objective of this study was to evaluate the induction of silicon tolerance in sorghum seeds submitted to abiotic stress. For silicon treatments, Sifol® (potassium silicate) was used in five doses (0.0, 0.3, 0.6, 0.9 and 1.2 g / L). For water stress simulation, the seeds were submitted to polyethylene glycol (PEG 6000) at concentrations of 0.0, -0.2, -0.4, -0.6 and -0.8 MPa and, for saline stress, sodium chloride (NaCl) was used at concentrations of 0, 75, 150 and 225 mM. The variables analyzed were: germination, first germination count, shoot and root length, shoot / root ratio and seedling dry mass. For germination, when subjected to saline stress there was reduction for both genotypes and when subjected to water stress genotypes EA03 and EA955 maintained germination close to 90% until the level of - 0,4 MPa and -0,6 MPa, respectively. . In saline stress silicon treatment maintained the first germination count of genotype EA03 above 90% and genotype EA955 around 60% in the highest NaCl concentration. For water stress, both genotypes showed reduction in the values of the first count. There was a reduction in shoot length for both genotypes in both saline and water stress. For root length for both water and saline stress the tested genotypes presented the best values at the concentration of 0.9 g / L Si. With the increase of saline and water stress there was a reduction in the shoot / root ratio. For the dry mass at 225mM concentration in genotype EA03 the best dry mass values were verified at the concentration of 0.9 g / L Si already for EA955 and in all silicon treatments were around 6 mg. For water stress both genotypes had a dry mass of around 6 mg. Silicon positively influenced the physiology of granular sorghum seeds, with the concentrations of 0.6 and 0.9 g / L presenting the best results.